The Implementation of The Values of Religious Moderation in the Local Content of Minangkabau Culture: A Gender Perspective at Bukittinggi Elementary School - Citra Dewi, Ayu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research explores the Implementation of Religious Moderation Values in Minangkabau Cultural Local Content. The local content focuses on character building based on the noble values of Minangkabau natural culture, namely PK-BAM. Using descriptive qualitative methods, data were collected through in-depth interviews with teachers and principals, direct observation of learning activities, and curriculum documentation studies. The collected data were analyzed using the Miles Huberman interactive model including data condensation, data presentation, and conclusion drawing. To ensure data validity, this study used triangulation. The results showed that the implementation of the PK-BAM curriculum has been running since 2022 in elementary schools in Bukittinggi City with learning once a week. The learning method combines face-to-face learning and direct practice of traditional values, involving traditional leaders such as ninik mama and bundo kanduang as guest teachers. Religious moderation means applying a balanced way of religion by prioritizing tolerance, respecting differences, upholding national values, and respecting local culture. Although the value of religious moderation is not explicitly listed in the textbooks, teachers creatively integrate it in learning. The PK-BAM curriculum influences students' understanding of cultural values and religious moderation. Students show appreciation of cultural values in daily life, respect religious and cultural differences and prioritize peace. The sustainability of the PK-BAM curriculum is ensured through the support of regional policies and the active involvement of community leaders, in line with the vision of “Bukittinggi Hebat” which is based on Adat Basandi Syarak and Syarak Basandi Kitabullah.